The observation of low concentrations of Co, Mn and Cr in urine samples of patients with breast tumours by GFAAS - Husáková, Lenka; Šrámková, Jitka; Daněk, Tomáš (Univerzita Pardubice, 2006)
A direct and quick method for the determination of Co, Mn and Cr in urine samples using graphite furnace atomic absorption spectrometry (GFAAS) has been developed. The effect of matrix for all elements studied was investigated on the typical solution according to the Dawson model. Metals in urine reference materials BIO-RAD Lyphochek of Level 1 and Level 2 were used to prove the reliability of the method applied. The detection limits estimated were... The method developed was used for the determination of the above-mentioned elements in urine samples of ten patients with breast cancer. Urine samples were analysed before and after surgery and the first chemotherapy. Comparison of Co, Mn and Cr levels prior to and after the treatment were performed using two-way analysis of variance (ANOVA) and Student's t-test. The experimental results have indicated that urinary levels of Mn and Cr analysed before surgery were different from those of controls while the differences between urinary Co concentrations of the same groups were not found to be statistically significant. Similarly, when levels before and after surgery and chemotherapy are compared, the former results of Mn and Cr were higher than in the later case and concentration levels of Co were not found to be significantly different (p=0.058). The urinary Mn was decreased also in control group of patients treated by a common, non-cancer surgery (p=0.018).
Keywords: atomová absorpční spektroskopie; grafitový atomizátor; moč; analytické stanovení; kobalt; mangan; chrom